86 GENE THERAPY BY POTENT GENERATION OF SPECIFIC CYTOTOXIC T LYMPHOCYTE AGAINST SPAN-XB/MULTIPLE MYELOMA. (1st January 2006) - Chiriva-Internati, M.; White, E.; Velez, B.; Grizzi, F.; Frezza, E.; Cobos, E.
Abstract : Purpose: Multiple myeloma (MM) is difficult to cure by conventional chemotherapeutic modalities but may be amenable to immunotherapeutic approaches. In past studies we have investigated the use of recombinant adeno-associated virus (AAV)-based vectors for their ability to effectively deliver viral antigen and cytokine genes into dendritic cells (DCs). Surprisingly rAAV/viral antigen-pulsing of DC stimulated significant cytotoxic T lymphocytes (CTL) with only one stimulation. Methods: Generation of the AAV-Spanxb virus stock, generation and infection of the DC to prime the nave T cell and by Facs analysis and Cr (51) to characterized the anti-Span-xb CTL. Summary: The generation of CTL against Span-xb antigens represents a more difficult challenge. In this study it is shown that rAAV/Span-xb antigen gene delivery into DC, with 7 days of T cell stimulation, resulted in (1) high MHC class I-restricted, antigen-specific CTL killing of target cells in 51 chromium release assays, (2) high levels of intra-T cell interferon g (IFN-g) expression, and (3) high levels of CD80, CD86, and CD40 expression on DC. Both synthetic, autologous Span-xb-positive targets and primary MM cell lines were good targets for killing by the anti-Span-xb CTL, while Span-xb-negative targets were not significant targets. Conclusion: These data suggest that rAAV/antigen gene pulsing of DC is a surprisingly effective technique for generating anti-self-antigen CTL as it is for viral antigens. Furthermore, these data suggest that Span-xb may be an effective antigen for targeting anti-MM CTL in gene therapy.